Modeling of Damage Interaction in Fatigue Relaxation for Long-Term Life Prediction. Case of Alloy 800 Grade 2 Study at 550°C - Gharad, A. El; Pluvinage, G.; Azari, Z.; Elamraoui, A.; Kifani, A. (Проблемы прочности, 2002)
Prediction of fatigue life in creep-fatigue at a
temperature of 550°C has been made for an
Inconel alloy with the help of 3 models of damage
evolution: the Chaboche model, the
Levaillant model, and a new model of creep fatigue
relaxation. The main advantages of the
new model are that it requires only few constants
and provides a high accuracy of the fatigue
life prediction. Прогнозирование усталостной долговечности в условиях ползучести при температуре 550°С
выполнено для жаропрочного и жаростойкого сплава на никелевой основе (Inconel). Представлены
модели эволюции повреждения Шабоша (Chaboche) и Леваяна (Levaillant), а
также новая модель релаксации при совместном действии ползучести и усталости. Предложенная
модель позволяет осуществлять долгосрочное прогнозирование без использования
большого количества постоянных. Прогнозування утомної довговічності в умовах повзучості при температурі 550°С виконано для жароміцного і жаростійкого сплаву на нікелевій основі (Inconel). Представлено методи еволюції пошкодження Шабоша (Chaboche) і Леваяна (Levaillant), а також нову модель релаксації при сумісній дії повзучості й утоми. За допомогою запропонованої моделі можна проводити довготермінове прогнозування без використання великої кількості сталих.